Imaging and Applied Optics 2014 2014
DOI: 10.1364/aio.2014.aw4a.3
|View full text |Cite
|
Sign up to set email alerts
|

Full-field Interferometric Confocal Microscopy using a VCSEL Array

Abstract: We present an interferometric confocal microscope using an array of 1200 VCSELs coupled to a multimode fiber. Spatial coherence gating provides ~18,000 continuous virtual pinholes allowing an entire en face plane to be imaged in a snapshot. This approach maintains the same optical sectioning as a scanning confocal microscope without moving parts, while the high power of the VCSEL array (~5 mW per laser) enables high-speed image acquisition with integration times as short as 100 µs. Interferometric detection al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…In this framing, the low spatial coherence is a consequence of using spatial multiplexing to perform highly parallelized confocal microscopy. We also note that the evidence suggests that the one-to-one relationship between source spatial mode and images resolution element can be relaxed at low to moderate levels of scattering [19,25].…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…In this framing, the low spatial coherence is a consequence of using spatial multiplexing to perform highly parallelized confocal microscopy. We also note that the evidence suggests that the one-to-one relationship between source spatial mode and images resolution element can be relaxed at low to moderate levels of scattering [19,25].…”
Section: Discussionmentioning
confidence: 73%
“…In a prior work, we used a multimode fiber to deliver light from the VCSEL array to the sample [25]. In this work, we used bulk-optic Köhler illumination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the decade that followed right up to the present day we see a broad array of research efforts, drawn from numerous communities, exploring interferometric detection of single nano-objects such as viruses, DNA, microtubules, exosomes, and proteins [75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91]. Interestingly, interferometric microscopies are also flourishing in the general context of label-free imaging of cells and membranes even if nanoparticles are not at the center of attention [75,76,90,[92][93][94][95][96][97][98][99][100][101][102][103][104][105][106]. The underlying physics of these methods remains the same although a plethora of acronyms such as interference reflectance imaging sensing (IRIS) [77], rotating coherent scattering (ROCS) [98], interference plasmonic imaging (iPM) [88], coherent bright-field imaging (COBRI) [107], stroboscopic interference scattering imaging (stroboSCAT) [108], interferometric scattering mass spectrometry (iSCAMS) [109] are on the rise.…”
Section: Historical Perspectivementioning
confidence: 99%
“…Similarly, the spatial-coherence gating effect has also been utilized in interferometric microscopy to obtain depth-resolved measurements [23]. B. Redding et al reported a fullfield interferometric confocal imaging method, where the spatial coherence was manipulated by using a multimode fiber [24]. The measured spatial resolution however was limited to a few microns.…”
Section: Introductionmentioning
confidence: 99%